Anatomical variations of median nerve formation, distribution and possible communication with other nerve in preserved human cadavers - Mat Taib, Che Norma; Hassan, Siti Nur Aisyah; Esa, Nurhidayah; Mohd Moklas, Mohamad Aris; San, Aye Aye (Via Medica, 2017)
Formation, distribution and possible communication of the median nerve are essential to know in treatment and surgeries of various conditions of injuries e.g. repair or reconstruction of the median nerve post traumatic accident. In the present study, 44 upper limbs were dissected. Root forming the median nerve, the median nerve in relation with the axillary artery and communication of the median nerve with other nerves were noted.